2021
DOI: 10.2151/sola.17a-002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Extremely Heavy Precipitation Induced by Typhoon Hagibis (2019) due to Historical Warming

Abstract: This is a PDF of a manuscript that has been peer-reviewed and accepted for publication. As the article has not yet been formatted, copy edited or proofread, the final published version may be different from the early online release.This pre-publication manuscript may be downloaded, distributed and used under the provisions of the Creative Commons Attribution 4.0 International (CC BY 4.0) license. It may be cited using the DOI below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Previous studies (Takemi and Unuma 2020) have assessed the immediate meteorological factors causing the heavy precipitation during the passage of Typhoon Hagibis and found that a nearly moist-adiabatic lapse rate, moist absolute instability, abundant moisture content, and high relative humidity throughout the troposphere jointly contributed to generating the heavy precipitation. Kawase et al (2021) took a step further and conducted an anatomy of the Typhoon (Hoerling et al 2013) and found that the historical warming intensified the strength of Typhoon Hagibis as well as the extreme heavy precipitation associated with the passing of the typhoon and that the topography of the area also contributed to the enhancement in total precipitation. However, this still leaves the question to what extent human-induced climate change has altered the likelihood of an extreme heavy precipitation event like the one associated with Hagibis from an impact perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Takemi and Unuma 2020) have assessed the immediate meteorological factors causing the heavy precipitation during the passage of Typhoon Hagibis and found that a nearly moist-adiabatic lapse rate, moist absolute instability, abundant moisture content, and high relative humidity throughout the troposphere jointly contributed to generating the heavy precipitation. Kawase et al (2021) took a step further and conducted an anatomy of the Typhoon (Hoerling et al 2013) and found that the historical warming intensified the strength of Typhoon Hagibis as well as the extreme heavy precipitation associated with the passing of the typhoon and that the topography of the area also contributed to the enhancement in total precipitation. However, this still leaves the question to what extent human-induced climate change has altered the likelihood of an extreme heavy precipitation event like the one associated with Hagibis from an impact perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Following Kawase et al (2021), we focus on precipitation, total column precipitable water (pwat) as a measure of moisture content throughout the atmospheric column, and sea level pressure (SLP)-to track minimum SLP as the central position of the typhoon. We use pwat and SLP to describe the environmental conditions during the passing of Typhoon Hagibis (shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, previous studies have explored alternative methods for studying climate change impacts on convective events. There are commonly two approaches: event‐driven (Armon et al., 2022; Hibino et al., 2018; Kawase et al., 2020, 2021; Lackmann, 2013; Takayabu et al., 2015) and climatological (Kawase et al., 2019; Lenderink et al., 2021; Liu et al., 2017; Prein, Rasmussen, et al., 2017). The former focuses on the study of a specific event under different conditions related to climate change, while the latter focuses on the general changes of this type of event on a climatological time scale.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the water vapor at about 1500 m asl is increasing, as is the number of days with precipitation exceeding 200 mm [2]. One study argued that the precipitation from Tropical Cyclone Hagibis, which fell over the Kanto area in October 2019, was higher by 10.9% due to the increase of ocean temperature [3]. Furthermore, record-breaking heavy rainfall events occur in Japan more frequently than before due to stagnant squall lines and other precipitation systems.…”
Section: Introductionmentioning
confidence: 99%